Identification of Body Length, Body Diagonal, Chest Circumference, and Shoulder Height of Female Priangan Sheep at SP3TDK Tambak Mekar Subang Regency - Al-Ayubi, Muhammad Habil; Heriyadi, Denie; Indrijani, Heni (Faculty of Animal Husbandry, Universitas Padjadjaran, 2025)
Abstract One of the indigenous sheep breeds that has flourished in Indonesia is the Priangan. The purpose of this study was to measure the female Priangan sheep's body size at SP3TDK Tambak Mekar in Subang Regency. 51 female sheep in all, 23 between the ages of 6 months and ≤1 year and 28 between the ages of 1 and 2 years, were used. Using a measuring tape and a measuring stick, measurements of shoulder height, chest circumference, body length, and body diagonal were made three times. Data were collected using the census method and analyzed descriptively. The results showed that the average body length of female Priangan sheep aged 6 months–≤1 year was 46.35 ± 4.61 cm, and those aged >1–2 years were 54.26 ± 3.77 cm. The average body diagonal was 50.26 ± 4.28 cm and 58.42 ± 3.06 cm, chest circumference 54.74 ± 4.96 cm and 62.91 ± 4.60 cm, and shoulder height 55.53 ± 3.78 cm and 62.11 ± 3.76 cm, respectively. It can be concluded that the body size of female Priangan sheep increases with age, indicating progressive growth that supports superior trait selection and productivity improvement.